Pelatihan Menjaga Gigi Kuat dan Gusi Sehat untuk Senyum Komunitas Penyintas Kanker ‘Kita Bahagia’ Jakarta Selatan - Caesary Cloudya Panjaitan; Sri Lestari; Trijani Suwandi; Eko Fibryanto; Florencia Livia (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
Cancer is the second-highest worldwide health problem that hasmortality rate after cardiovascular disease. Chemotherapy and radiotherapy are the most frequently used treatments by patients with known side effects on dental and oral health, such as brittle teeth, bleeding gums, and dry mouth, making it difficult for patients to perform therapy and lower the body's resistance. This community service (PkM) was carried out boldly in the Cancer Survivor Community 'Kita Bahagia' to increase knowledge about maintaining dental and oral health after therapy. This PkM was attended by 55 participants for 3 hours. The material given is about the impact of post-therapy on the hard and soft tissues of the oral cavity and maintaining dental and oral health regularly in the form of power points, e-flyers, and interested videos. The training was evaluated by undertaking a pre-post test containing 20 oral health questions. There was an increase in participants' knowledge of 17.28% within an average pre-test score of 61.27% to 78.55% in the post-test. The participants were very enthusias, as seen from the many questions asked during the live activities and via chat zoom. Within this activity, we hoped that the dental and oral health of post-therapy cancer survivors can be well maintained with good application and to other community members, families, and the wider community.